The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1159/000359924
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Aging and Alzheimer's Disease on Emotional Enhancement of Memory

Abstract: Emotional enhancement of memory (EEM) has been a well-known phenomenon which corresponds to the advantage of emotional stimuli to be better recalled than neutral ones. Previous studies suggest that aging favours recollection of positive items and this pattern is disrupted in Alzheimer's disease (AD). Emotional valence of different stimulus modalities, i.e. pictures and words, may also have an effect on each other's memory performances. However, none of these were clearly studied in AD. This study aimed to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 56 publications
0
7
1
Order By: Relevance
“…In this study, emotional memory enhancement effect (Hamann, 2001;Buchanan and Adolphs, 2002;Buchanan, 2007;Baran, Cangöz and Özel Kızıl, 2014) emerged for negative photograph, but not for positive photograph. Although some studies have found positive events/stimulus to be remembered better than neutral ones (D' Argembeaue et al, 2003;Comblain et al, 2005;Kensinger and Schacter, 2006;Yegiyan and Yonelinas, 2011;Chipchase and Chapman, 2013), this was not found in our study as there was no difference in remembering central and peripheral details of positive and neutral events.…”
Section: Discussion Related With Effects Of Emotioncontrasting
confidence: 47%
“…In this study, emotional memory enhancement effect (Hamann, 2001;Buchanan and Adolphs, 2002;Buchanan, 2007;Baran, Cangöz and Özel Kızıl, 2014) emerged for negative photograph, but not for positive photograph. Although some studies have found positive events/stimulus to be remembered better than neutral ones (D' Argembeaue et al, 2003;Comblain et al, 2005;Kensinger and Schacter, 2006;Yegiyan and Yonelinas, 2011;Chipchase and Chapman, 2013), this was not found in our study as there was no difference in remembering central and peripheral details of positive and neutral events.…”
Section: Discussion Related With Effects Of Emotioncontrasting
confidence: 47%
“…As such, people diagnosed with neurodegenerative diseases improve their self-esteem and well-being by using creative activities by means of acts of making, which produce pleasure and reduce anxiety Byers et al [3,5,[21][22][23][24][25]. This is likely because neurodegenerative diseases have an impact on the human memory and decrease cognitive faculties, but emotions and affect are less impacted by degeneration Baran et al [26][27][28][29][30][31]. Fundamental properties of artistic technique can then be used to help people participate in the therapeutic process, and people affected by such diseases remain sensitive to subjective art-based experiences Camic et al [5,[32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews have also suggested that creative art therapy is effective for the treatment of behavioural and emotional challenges resulting from the diseases Cowl et al [4,37,38], and an emotional enhancement of memory effect has been seen in people with neurodegenerative diseases Baran et al. [26,39,40]. It also appears that positive emotions broaden the scope of action and build physical resources Fredrickson [41].…”
Section: Introductionmentioning
confidence: 99%
“…Sava et al (2015) demonstrated that AD patients had a positive memory bias when the stimulus was sufficiently rich and deep encoded to the individual, and when support was provided the time of retrieval such as cued recall or recognition tasks. Another free-recall study highlighted the impaired EEM for verbal stimuli but preserved EEM for non-verbal declarative memory in patients with mild AD (Baran et al, 2014). These discrepancies may be a result of different materials used to elicit the emotional response, different arousal of stimuli, and also different encoding and retrieval methods used in each specific study.…”
Section: Introductionmentioning
confidence: 99%